TUHAN KAUM MISTIK: Kontribusinya Bagi Toleransi Ummat Beragama - Yunus, Muhammad; Ngimadudin, Ngimadudin (El-Ghiroh : Jurnal Studi Keislaman, 2022)
This study aims to explore the concept of God for the mystics and its contribution to religious tolerance in Indonesia. The questions to be answered in this research are (1) What is the concept of God for the Mystics ?, (2) What and how does the concept contribute in relation to religious tolerance, especially in Indonesia. This research is a qualitative research. The data source comes from the literature. The analysis method uses a hermeneutic which consists of elements of description and interpretation. The results of this study found that the God of the mystics is an impersonal God, in the sense of not being described. Another reality besides Him is His image. He is One and the cause of everything. He can only be found or approached by those who have purified themselves. The contribution of the mystics to the tolerance of the religious community lies in the similarity of their conception of God, namely as God who is undefined. This similarity can be used as a meeting point that allows the Religious community to be more inclusive and enlarge the equation, not the other way around